Pancasila dan Isu Kemanusiaan : Antara Penegakan Hukum dan Tanggung Jawab Kemanusiaan dalam Menyikapi Undocument Migrant - Hafandi, Raisha; Meritasari, Dini Putri Ratna (Universitas Muhammadiyah Ponorogo, 2026)
The phenomenon of undocumented migrants is a global humanitarian issue that places states in a dilemma between the obligation to enforce immigration laws and the humanitarian responsibility to uphold human rights. Indonesia, as a state founded on Pancasila, faces challenges in formulating policies and practices for addressing undocumented migrants that are not only oriented toward legal–formal aspects but also reflect humane and ethical values. This study aims to analyze how the values of Pancasila can serve as an ethical and normative framework in responding to the presence of undocumented migrants, particularly in the context of the relationship between law enforcement and the state’s humanitarian responsibility. This research employs a qualitative method with a normative–empirical approach, utilizing literature review of national and international regulations as well as case analysis of undocumented migrant handling in Indonesia. The findings indicate that immigration law enforcement practices still tend to position undocumented migrants merely as objects of legal violations, potentially neglecting humanitarian principles as embodied in the second and fifth principles of Pancasila. Therefore, a more integrative and humane policy approach is required, with Pancasila serving as the foundational basis for balancing legal certainty, human rights protection, and the state’s humanitarian responsibility. This study is expected to contribute conceptually to strengthening the Pancasila-based perspective in the formulation of just and civilized migration policies.